Where should siRNAs go: applicable organs for siRNA drugs - Insook Ahn; Chanhee S. Kang; Jinju Han (Experimental and Molecular Medicine, 2023)
Abstract RNA interference mediated by small interfering RNAs (siRNAs) has been exploited for the development of therapeutics. siRNAs can be a powerful therapeutic tool because the working mechanisms of siRNAs are straightforward. siRNAs determine targets based on their sequence and specifically regulate the gene expression of the target gene. However, efficient delivery of siRNAs to the target organ has long been an issue that needs to be solved. Tremendous efforts regarding siRNA delivery have led to significant progress in siRNA drug development, and from 2018 to 2022, a total of five siRNA drugs were approved for the treatment of patients. Although all FDA-approved siRNA drugs target the hepatocytes of the liver, siRNA-based drugs targeting different organs are in clinical trials. In this review, we introduce siRNA drugs in the market and siRNA drug candidates in clinical trials that target cells in multiple organs. The liver, eye, and skin are the preferred organs targeted by siRNAs. Three or more siRNA drug candidates are in phase 2 or 3 clinical trials to suppress gene expression in these preferred organs. On the other hand, the lungs, kidneys, and brain are challenging organs with relatively few clinical trials. We discuss the characteristics of each organ related to the advantages and disadvantages of siRNA drug targeting and strategies to overcome the barriers in delivering siRNAs based on organ-specific siRNA drugs that have progressed to clinical trials.